Properties of Sago Particleboards Resinated with UF and PF Resin - Tay, C.C.; Hamdan, S.; Osman, M.S.B. (Hindawi Publishing Corporation, 2016)
The sago processing industry in Mukah, Sarawak, had generated huge amount of sago waste after the milling process and scientists have employed the waste into composite material. In this work, sago residues were mixed with the Phenol Formaldehyde (PF) and Urea Formaldehyde (UF) for particleboard fabrication. The fabrication and testing methods are based on JIS A 5908 Standard. A single layer particleboard using sago particles was fabricated at targeted density of 600 kg/m3. Particles with weight fractions of 90%, 85%, and 80% with two different matrices were used in the fabrication. The results demonstrated that the samples with different weight fraction and matrix have great influence on the mechanical properties such as MOR, MOE, Young's Modulus, tensile strength, impact strength, screw test, and internal bonding. The sago UF/PF particleboard only displays single stage decomposition. All the panels underwent physical tests which are water absorption and thickness swelling. The combination of sago particles with UF/PF can be utilized for general indoor application purposes such as furniture manufacturing. Sago particleboard made by UF/PF provided the advantages like optimized performance, minimized weight and volume, cost effectiveness, chemical resistance, and resistance to biodegradation.